Grey Water and Black Water Wastewater Policy in Improving the Quality of Environmental Management in Gorontalo City, Indonesia - Karim Kasim, Kartika; M. Wantu, Sastro; Ilato, Rosman; Abdussamad, Juriko (Indonesian Association for Public Administration (IAPA), 2024)
This study aims to look at the implementation process of gray water and black water wastewater management policies in Gorontalo City in the context of improving environmental quality. The method used is a descriptive qualitative approach with the Miles and Huberman model technique in the form of data collection through field observation, analysis of documents from related agencies and interviews with resource persons by providing a structured questionnaire so as to obtain research results by reconstructing policies that show that the implementation of centralized wastewater management policies in northern cities using Charles O. Jones' theory by looking at factors The following are the following: (1) The organization still faces several significant obstacles, such as the lack of adequate wastewater management infrastructure, (2) The interpretation of the government's weak commitment in monitoring and maintaining IPALT facilities made by the Directorate of Cipta Karya, In addition, the enforcement of regulations such as Mayor Regulation Number 9 of 2016 has not been effective due to the lack of supervision of the community who dump domestic wastewater into the river so that the sanctions given by violators neglected policies. (3) Application In the implementation process, it turned out that there was a lack of budget given to DLH (Environmental Service) so that it did not run properly and optimally, so that development (IPALT) did not function optimally. This study recommends more equitable infrastructure improvements, increased budget allocation, and strengthening sanctions against communities that pollute water with wastewater, Novelty for the success of gray water and black water wastewater management to improve the quality of the environment in Gorontalo City is the existence of a more appropriate wastewater management method that is clearly explained in the policy so that waste management is more effective and sustainable. to create a cleaner and healthier environment in Gorontalo City. Achievable